The painted castle - Cambron, Kristy (A Lost Castle novel, 2019)
When art historian Keira Foley is hired to authenticate a painting at a centuries-old East Suffolk manor, she hopes this is just the thing to get her career and life back on track. But from the time she arrives at Parham Hill Estate and begins working alongside rumored art thief Emory Scott, she<U+2019>s left with far more questions than answers. Could this lost painting of Queen Victoria be a duplicate of the original Winterhalter masterpiece, and if so, who is the artist? As Keira begins to unravel the mystery behind the portrait, two women emerge from the estate<U+2019>s forgotten past. In Victorian England, talented sketch artist Elizabeth Meade is engaged to Viscount Huxley, then owner of Parham Hill. However, Elizabeth<U+2019>s real motive for being at Parham Hill has nothing to do with art or marriage. She<U+2019>s determined to avenge her father<U+2019>s brutal murder<U+2014>even if it means a betrothal to the very man she believes committed the crime. A century later, Amelia Woods<U+2014>a World War II widow who has turned Parham Hill and its beloved library into a boarding school for refugee children<U+2014>receives military orders to house a troop of American pilots. She is determined the children in her care will remain untouched by the war, but the task is proving difficult with officers taking up every square inch of their world . . . and one in particular vying for a space in Amelia<U+2019>s long-shut up heart. Set in three time periods<U+2014>the rapid change of Victorian England, the peak of England<U+2019>s home-front tensions at the end of WWII, and modern day<U+2014>The Painted Castle unfolds a story of heartache and hope and unlocks secrets lost for generations just waiting to be found.